Identifikasi dan Penetapan Kadar Senyawa Kuinin Fraksi Etil Asetat Kulit Batang Kina (Cinchona succirubra Pav. Ex Klotzsch) Secara KLT-Densitometri - Gede Sugiartha Giri (Ikatan Senat Mahasiswa Farmasi Seluruh Indonesia, 2020)
Alkaloids quinine is found in the quinine plant which is the raw material for the manufacture of quinine pills that are effective in the treatment of malaria. Selection of the method, solvent, identification technique and characterization of the alkaloid quinine compound in the quinine plant (Cinchona succirubra Pav. Ex Klotzsch) need to be done in an effort to produce the compound with the best separation.Extraction by maceration method, identification of groups using phytochemical screening methods. Fractionation using liquid-liquid extraction method and column chromatography. Isolation using preparative chromatography method and TLC-Densitometry method. Maceration extraction obtained the filtrate with a reddish brown color. Phytochemical screening was positive for triterpenoids and alkaloids. Liquid-liquid extraction resulted in the water fraction, ethyl acetate fraction I, and ethyl acetate fraction II. TLC and identification of positive chemical reactions containing quinine in ethyl acetate fraction II. Column chromatography obtained results in the form of 4 fractionations with different colors. Preparative chromatography and compound isolation by TLC-Densitometry showed the average quinine content of ethyl acetate fraction was 15.30%. The ethyl acetate fraction of quinine stem bark (Cinchona succirubra Pav. Ex Klotzsch) produced average quinine alkaloids of 15, 30% according to the cultivated kina plant which contains up to 15% quinine alkaloids.